PTU-008 Enhancing professional behaviour in gastrointestinal endoscopy: development of a behavioural marker tool for assessment of endoscopic non-technical skills. (23rd September 2015) - Haycock, A; Woolf, K; Thomas-Gibson, S
Abstract : Introduction: Renewed focus on patient safety has highlighted the need for competency based assessment and training in medicine. Much of the current emphasis is on improving training and assessment of technical skill. However, work in other high-risk industries such as aviation show that errors and adverse outcomes are often not due to failure of technical skill, but other factors such as breakdown in communication and poor decision making, which are often termed "non-technical skills". Two qualitative studies were performed; the first defined a taxonomy of non-technical skills specific to gastrointestinal endoscopy. The second developed a tool based on observable behavioural markers which can be used for assessment and training purposes. Methods: In a semi-structured interview study, nine consultant endoscopists were asked to recount an actual critical incident to elicit examples of where human factors were implicated in situations that have adversely affected patient safety in endoscopy. Transcripts of the interviews were analysed using a framework approach from which a non-technical skills taxonomy was developed. This taxonomy was then used to identify behavioural markers from four quad-split video recordings of bowel cancer screening colonoscopy lists. These markers were grouped together to produce a behavioural marker assessment tool. Results: The interview analysis gave rise to a taxonomy of 33 non-technical skills in 14 categories. These were divided into general skills (Communication, Teamwork, Leadership, Confidence, Emotional Control), pre-procedural skills (Planning), procedural skills (Assessing situation, Judgement and Decision-making, Focus, Awareness, Problem Recognition, Problem Management, Responsibility), and post procedural skills (Responsibility, Reflection). Review of the colonoscopy recordings using this taxonomy elicited examples of 13 behavioural elements in four general categories (Communication and Teamwork, Situation Awareness, Leadership, Judgment and Decision Making). Directly observed examples of good and poor behaviour were mapped to all but four of the 33 non-technical skills identified in the interview study. Conclusion: These two qualitiative studies have produced a tool to allow assessment and feedback regarding key observable non-technical skills needed by gastrointestinal endoscopists. The tool will need to be validated in a wider range of endoscopy practise both in terms of level of competence (construct validity) and different endoscopic procedures. It can potentially be used alongside a knowledge and technical skills training and assessment to provide more complete training and evaluation of professional behaviour within this field.